2021
DOI: 10.1037/pas0001011
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Connor-Davidson Resilience Scale 10 (CD-RISC-10) using the polytomous Rasch model.

Abstract: The Connor-Davidson Resilience Scale's (CD-RISC) 10 item variant has previously demonstrated acceptable psychometric properties of its test scores using traditional methods (e.g., confirmatory factor analysis), and concurrent validity with resilience-related outcomes, particularly in samples of younger adults. While alternative methods of examining the psychometric properties of the long-form CD-RISC exist in the literature, the short-form measure has unclear evidence of local item independence and a unidimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 39 publications
5
14
0
Order By: Relevance
“…Future studies should utilize IRT-based item-level diagnostics of old and new resilience measures to test varying salience of different flavors of resilience among persons responding to one adversity versus another. High ceiling effects reported in past studies such as Heritage et al [ 46 ], now corroborated by our findings, call for fresh, innovative measures incorporating items that conceptually reflect and psychometrically capture the sentiments of highly resilient persons more efficiently than CD-RISC scales do.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Future studies should utilize IRT-based item-level diagnostics of old and new resilience measures to test varying salience of different flavors of resilience among persons responding to one adversity versus another. High ceiling effects reported in past studies such as Heritage et al [ 46 ], now corroborated by our findings, call for fresh, innovative measures incorporating items that conceptually reflect and psychometrically capture the sentiments of highly resilient persons more efficiently than CD-RISC scales do.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, Rasch analyses by Pulido-Martos et al (2020) on a sample of Spanish citizens ( N = 1011) confirmed CD-RISC-10’s unifactorial structure [ 45 ]. Nevertheless, Heritage et al (2021)’s Rasch rating scale model study among Canadian/Australian nursing students ( N = 708) did not support a unifactorial model, leading authors to propose a 7-item abbreviation [ 46 ]. Despite extant literature suggesting the graded response model (GRM) [ 47 , 48 ] is a superior approach for Likert scales [ 49 , 50 ], most IRT analyses of the CD-RISC-10 apply Rasch models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and the method of assessment. 12 A critical review of scales that are most frequently used for the assessment of resilience identified the Connor-Davidson Resilience Scale (CD-RISC) 13 as the most useful and robust of these measures. 11 The CD-RISC comprises 25 items that are scored on a 5-point scale.…”
Section: Introductionmentioning
confidence: 99%
“…24,25,27 However, sufficient evidence confirming the instrument's item independence and unidimensional structure remains lacking. 12 For this reason, 12 Heritage et al used the Rasch model approach to analyze the properties of the CD-RISC-10 and proposed a seven-item version of the scale. The Rasch model has certain advantages over other approaches including its ability to precisely predict the mathematical association between an item and a latent trait to be measured.…”
Section: Introductionmentioning
confidence: 99%